From Olympus to Camelot : the world of European mythology - Leeming, David Adams, 1937- (OUP E-Books., 2003)
From the stories suggested by the great cave paintings of the Paleolithic period to the thought experiments of modern scientists, From Olympus to Camelot provides a sweeping history of the development of the rich and varied European mythological tradition. David Leeming, an authority on world mythology, begins with a general introduction to mythology and mythological terms, and then turns to the stories themselves. Discussing well-known figures such as Zeus, Aphrodite, Thor, and Cuchulainn, and less familiar ones such as Perun, Mari, and the Sorcerer of Lescaux, Leeming illustrates and analyzes the enduring human endeavor to make sense of existence through deities and heroes. Following an initial exploration of the Indo-European sources of European mythology and the connections between the myths of Europe and those of India and Iran, the book proceeds to survey the major beliefs of Greek, Roman, Celtic, Germanic, Baltic, and Slavic cultures, as well as the mythologies of non-Indo-European cultures such as the Etruscans and the Finns. Among its contents are introductions to the pantheons of various mythologies, examinations of major mythological works, and retellings of the influential mythical stories. This work also examines European deities, creation myths, and heroes in the context of Christian belief, and considers the translation of traditional stories into the mythologies of modern European political, scientific, philosophical, and economic movements. European mythology is the core mythology of Western civilization. This wide-ranging volume offers a lively and informative survey, along with a provocative new way of understanding this fundamental aspect of European culture.